2021
DOI: 10.21203/rs.3.rs-871607/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergency Services Utilization in Jakarta (Indonesia): A Cross-Sectional Study of Patients Attending Hospital Emergency Departments

Abstract: Background Pre-hospital and emergency services in Indonesia are still developing. Despite recent improvements in the Indonesian healthcare system, issues with the provision of pre-hospital and emergency services persist. The demand for pre-hospital and emergency services has not been the subject of previous research and, therefore, has not been fully understood. Our research explored the characteristics of patients attending hospital emergency departments in Jakarta, Indonesia. Methods The study used a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In this Haitian study, the highest proportion (64%) arrived directly from their homes and the lowest (2%) from a market. Further data from only three studies in Australia, Switzerland, and the UK reported consistently low presentations of patients from nursing homes, ranging from 0.9-2% [13,14,15].…”
Section: Resultsmentioning
confidence: 95%
“…In this Haitian study, the highest proportion (64%) arrived directly from their homes and the lowest (2%) from a market. Further data from only three studies in Australia, Switzerland, and the UK reported consistently low presentations of patients from nursing homes, ranging from 0.9-2% [13,14,15].…”
Section: Resultsmentioning
confidence: 95%